Análise multitemporal do uso e cobertura da terra no Município de Primavera-Pa, utilizando os dados do mapbiomas de 1985 a 2023 - SILVA, Paula Elayane Farias da (2024)
There are several factors that demonstrate the action of man on nature, which is perceived according to its specificities and the means applied. Therefore, the present work aims to analyze land use and coverage, through data available on the MAPBIOMAS BRASIL v 9.0 platform, from 1985 to 2023. In view of the above, the municipality selected for analysis is Primavera/PA. The choice of this municipality as the unit of analysis is particularly relevant, given the impact of human activities, such as the installation of a Votorantim cement factory (installed in 2016); as well as advances in environmental preservation with the creation of the Filhos do Mangue Marine Extractive Reserve (2024), which have directly influenced land use and local environmental characteristics; another important point is the lack of geospatial information in the research area. Thus, the importance of research in the municipality for analyzing environmental issues such as economic and social is evident. The methodology consisted of bibliographic and documentary research, and the use of software for classification through the Qgis 3.32 software, categorization was done by the color palette, together with vectorization, resulting in the generation of thematic maps classified at different time moments. The results obtained showed that the use and occupation of the land in the municipality in 1985 were mainly constituted by forest formation (90%), and even after the industrial and agricultural advances, we observed that in 2023 the forest formation class prevails to a greater extent (60%), but it is evident that the municipality has been showing a loss in its forest formation with the increase in anthropic actions, especially related to agriculture and urban development, resulting in a landscape and economic change in the region.